Biogas upgrading and liquefaction in an anaerobic digester plant. (August 2018) - Baccioli, A.; Ferrari, L.; Marchionni, A.; Desideri, U.
Abstract: Thanks to the high energy density and to the extended range it can ensure, LNG is an attractive energy vector especially in heavy-duty transportation. This fuel is even more interesting if produced starting from biogas because of the reduced carbon footprint. Biogas production occurs in anaerobic digestion plants and various production strategies can be pursued to transform biogas into bio-LNG. In this study the anaerobic digester of the municipal wastewater treatment plant of Viareggio has been analyzed. The plant is equipped with a Capstone C600s co-generative micro gas turbine and with a boiler for the sludge heating. Three different bio-LNG production strategies have been considered. In the first strategy (the baseline case), the biogas fueled boiler provides the heat necessary for the sludge heating. The electric energy required for wastewater treatment and for upgrading and liquefaction processes is bought from the electric grid. In the second strategy, the micro gas turbine is operated in thermal following mode and the electric energy required by the plant processes is partly self-produced and partly acquired from the grid. In the third strategy, the micro-turbine is operated in electric following mode, attempting to cover all the electric load necessary to the process and part of the heat necessary to the sludge heating. The plant was analyzed in steady-state conditions by considering the heat requested by the anaerobic digesters, the efficiency curves of the micro gas turbine and the boiler, and the heat exchangers off-design behavior. Results showed that, according to the economic reference scenario, the solution with the high profitability can be that with the boiler of that with the micro gas turbine operated in thermal following mode.